Equilibrium, Kinetic and Thermodynamic Studies on Adsorption of Penoxsulam in Punjab Soils. Issue 5 (4th July 2022) - Kaur, Pervinder; Shilpa,; Kaur, Harshdeep; Bhullar, Makhan Singh
ABSTRACT: Adsorption desorption behavior of herbicide in soil plays important role in assessing the fate of herbicide. Batch equilibrium method was used to assess the effect of physicochemical properties of soil and temperature on adsorption-desorption of penoxsulam in Punjab soils under laboratory conditions. The adsorption of penoxsulam in studied soils followed pseudo-second-order kinetics and fitted well into Freundlich and Langmuir model. Freundlich adsorption coefficient varied from 0.858 to 1.585 µg 1−1/n g −1 ml 1/n indicating strong binding of penoxsulam on soil matrix. Adsorption increased with increase in temperature and thermodynamic parameters showed that adsorption process was feasible, spontaneous and endothermic. Desorption was slow with hysteresis coefficient ranging from 0.016 to 0.207. Adsorption was dominant by surface adsorption at low equilibrium concentration while partition at high equilibrium concentration. Principal component analysis (PCA) indicated that penoxsulam was moderately mobile in soil and can potentially contaminate groundwater. Highest leachability of penoxsulam was in loamy sand followed by sandy loam, loam, silt loam and clay loam. Remedial methods like the addition of organic amendments helps in reducing downward movement of penoxsulam and avoid its potential adverse effects.